THE ART OF ORNAMENTED FELT OF THE NOGAIS - Kuzeeva, Zuhra Zalimhanovna; Zel'nickaa (Slarba), Rica Sotovna (History, Archeology and Ethnography of the Caucasus, 2018)
The article studies the traditional Nogai felt like a monument of folk art from the point of view of ethnography and art criticism. The problem has arisen as a distinctive cultural phenomenon due to the challenges posed by modern society today. Unfortunately, in the era of urbanization and the introduction into the environment of new technologies, the emergence and spread of “fashion” on various cultural trends coming both from the West and from the Islamic East, the decline of traditional culture among the masses is natural. The threat of the disappearance of traditional crafts of small peoples may lead to the unification of their national culture and the loss of their ethnic identity. The study of topical issues at the theoretical level is a prerequisite for the preservation and development of ethnocultural traditions - an important component of peoples’ spiritual values.The description of groups of traditional Nogai felt products (felt to cover the yurt, felt of the yurt interior, felt ceremonial outfit for horses, camels), as well as a detailed analysis of the felt-making technique, how to decorate it, and the structure of the ornament are presented to readers’ attention. Analogs are given with the felt products of the peoples of Central and Eastern Asia, Kazakhstan, Siberia, Eastern Europe, and the Caucasus, which speaks of their common cultural and historical past.The article is based on a comprehensive analysis of materials of the XIX-XX centuries, discovered by the authors during the expedition surveys in 2014-2016 in various settlements of Dagestan, Chechnya, Stavropol region, Karachay-Cherkessia, Astrakhan region, where the Nogais live in compact communities; museum collections of St. Petersburg, Astrakhan, Cherkessk, Stavropol, Makhachkala, Kizlyar, as well as historical sources and literary information.
Keywords: Keywords; the Nogais; felt; kiyiz; traditional art; spiritual and cultural values; globalization; unification; problems of preservation and development.